The Management Compensation, Profitability and Environmental Performance Against Voluntary Disclosure: an Empirical Study on the Manufacturing Industry in Indonesia - Aulia, Triana Zuhrotun; Alamsyah, Sustari; Eko Narto Utomo (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This study empirically examines the effect of management compensation, profitability and environmental performance on voluntary disclosure in order to provide information about company activities which are expected to be a good signal for investors in improving the company's good image and reducing asymmetric information. The population used are companies listed on the IDX for the basic manufacturing and chemical sub-sector 2015-2019. Criteria Based on purposive sampling, 11 companies became the research sample. The data analysis method used panel data regression analysis with the eviews 9.0 program which consisted of making research models (CEM, FEM and REM), selecting the model used (Chow test, Hausman test and LM test), and hypothesis testing using t test and f test. The results of the study prove that management compensation and environmental performance have an effect on voluntary disclosure, while profitability has no effect on voluntary disclosure.